New frontiers in artificial intelligence : JSAI-isAI International Workshops, JURISIN, AI-Biz, LENLS, Kansei-AI, Yokohama, Japan, November 10-12, 2019, Revised selected papers /: JSAI-isAI International Workshops, JURISIN, AI-Biz, LENLS, Kansei-AI, Yokohama, Japan, November 10-12, 2019, Revised selected papers. (2020) - Unknown
No abstract available